Effect of cassava starch on shrinkage characteristics of concrete†. Issue 4 (7th June 2019) - Akindahunsi, Akindehinde Ayotunde; Schmidt, Wolfram
Abstract : The use of starch and its derivatives in concrete as an admixture to modify relevant properties of concrete has been on the increase in recent times. It is known to modify the rheology, affect the hydration kinetics of cement, and influence initial and final setting times of cement. This paper examines the effect of cassava starch on shrinkage properties of concrete. Concretes with and without starch additions, were investigated. Various percentages (0, 0.5, 1.0, 1.5 and 2.0%) of starch by weight of cement were added to concrete mixes prepared in the laboratory. Shrinkage tests were conducted for a duration of up to one year. The results show that concretes with starch additions exhibit lower shrinkage, which is an indication that the addition of starch as an admixture in concrete improves the ability of the concrete to reduce shrinkage problems.